Leaders and masses in the Roman world : studies in honor of Zvi Yavetz - Yavetz, Zvi, 1925-2013.; Malkin, Irad.; Rubinsohn, Z. W. (Mnemosyne, Supplements, 1995)
It is largely thanks to Zvi Yavetz that the Roman plebs has become "Salonfähig". In numerous important studies Yavetz has focused his - and our - attention on the problem of the relationship between the ruler and the masses of the ruled. Thus, it seemed natural to choose various aspects of this relationship as the topic of a volume in his honour. The articles here contributed by thirteen eminent friends and colleagues deal with historical and theoretical questions of the relationship between "the one" and "the many", covering a period from the second century B.C., through the times of the Late Republic and the Principate, to Late Antiquity and, finally, to an intriguing view at modern totalitarianism as perceived from an Enlightenment perspective.